Antibacterial Activity of Simpur Leaves Methanol Extract (Dillenia sp.) Againts Staphylococcus aureus - Shafira Qurrata A'yuni; Rikhsan Kurniatuhadi; Zulfa Zakiah (Universitas Sam Ratulangi, 2025)
Simpur (Dillenia sp.) is a plant that can be used as traditional antibacterial medicine. This study aims to determine the inhibitory activity of Staphylococcus aureus bacteria when exposed to a concentration of methanol extract from Simpur leaves (Dillenia sp.). This study utilized a completely randomized design with five concentration levels of Dillenia sp. specifically, the study included a control group and methanol extracts of Simpur leaves at concentrations of 5%, 10%, 15%, and 20%. The methods used included total plate count, hemocytometer, and UV-Vis spectrophotometry, which were then analyzed using ANOVA (Analysis of Variance). The results showed that the greatest inhibition occurred in the methanol extract of Simpur leaves (Dillenia sp.) at a concentration of 20%, there was a decrease in the number of colonies ranging from 90% to 94%, while the decrease in the number of cells ranged from 17% to 18%. The lowest inhibition was found in the methanol extract of Simpur leaves (Dillenia sp.) with a concentration of 10%, the proportion of decreasing the number of colonies ranged from 63% to 70%, while the proportion of decreasing the number of cells ranged from 6% to 7%. The highest optical density (OD) value at a 20% concentration ranged from 0.482 to 0.547, while the lowest value at a 5% concentration ranged from 0.127 to 0.131. The conclusion of this study is that the methanol extract of Simpur leaves (Dillenia sp.) Bacteriostatic antibiotics only inhibit bacterial growth and cannot kill bacteria.